Used Car Sale Application Design in Car Shoowroom Using Extreme Programming - A. Ferico Octaviansyah Pasaribu; Agung Deni Wahyudi (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2023)
Information technology is an activity of collecting, processing, managing, storing, disseminating and utilizing information. Apart from involving hardware and software, this technology also pays attention to human interests in its utilization. Car Showroom is a company engaged in buying and selling used cars. As a growing company and from its stagnant sales chart data for the last 5 years, Car Showroom took the initiative to make the internet a marketing medium. Judging from the reality, so far it has been difficult to provide information regarding the product. Making it easier to design a system that is created, as well as implementing a used car sales application in a car showroom made using the PHP programming language with the MySql database so that the information held by the showroom can be accessed by users online and in real time. With this application, it can help users find used cars online. Based on the results of the recapitulation of the 7 testing criteria that have been carried out, the results show that the number of answers from respondents has a value of 100% in accordance with testing system functionality using blackbox testing.